Preconditioning with interleukin‐1 beta and interferon‐gamma enhances the efficacy of human umbilical cord blood‐derived mesenchymal stem cells‐based therapy via enhancing prostaglandin E2 secretion and indoleamine 2, 3‐dioxygenase activity in dextran sulfate sodium‐induced colitis. (25th July 2019) - Yu, Yeonsil; Yoo, Sae Mi; Park, Hwan Hee; Baek, Song Yi; Kim, Yoon‐Jin; Lee, Seunghee; Kim, Yu Lee; Seo, Kwang‐Won; Kang, Kyung‐Sun
Abstract: Preconditioning with inflammatory cytokines has improved mesenchymal stem cells characteristics, including differentiation and immunomodulating functions. In this study, we developed a preconditioning combination strategy using interleukin‐1beta (IL‐1β) and interferon‐gamma (IFN‐γ) to enhance the immuneregulatory ability of human umbilical cord blood‐derived mesenchymal stem cells (hUCB‐MSCs). Our results showed that hUCB‐MSCs preconditioned with IL‐1β and IFN‐γ (primed hUCB‐MSCs) created a statistically significant decrease in peripheral blood mononuclear cell proliferation, indicating that their immunosuppressive ability was increased. The secretion of PGE2, cyclooxygenase 2 mRNA expression, and indoleamine 2, 3‐dioxygenase (IDO) mRNA expression in primed hUCB‐MSCs was significantly higher than those in the untreated hUCB‐MSCs or the IL‐1β or IFN‐γ only treated hUCB‐MSCs. When inhibitors of IDO and PGE2 were treated, peripheral blood mononuclear cell proliferation, which is inhibited by primed hUCB‐MSCs, was recovered. We found that Th1 T cell differentiation was also inhibited by PGE2 and IDO in the primed hUCB‐MSCs, and Tregs differentiation was increased by PGE2 and IDO in the primed hUCB‐MSCs. Furthermore, the primed hUCB‐MSCs as well as supernatants increase CD4 + T cells migration. We demonstrated the therapeutic effects of primed hUCB‐MSCs in dextran sulfate sodium‐induced colitis model. In conclusion, we have demonstrated that primed hUCB‐MSCs simultaneously enhance PGE2 and IDO and greatly improve the immunoregulatory capacity of MSCs, and we have developed an optimal condition for pretreatment of MSCs for the treatment of immune diseases. Our results raise the possibility that the combination of PGE2 and IDO could be therapeutic mediators for controlling immunosuppression of MSCs.